Essays on banking and finance in Nigeria - Otiti, A. O. G. (Lagos : CIBN Press, 1998)
Essays on banking and finance in Nigeria discusses the role of agriculture; the role of CBN; role of unit trust in capital market development; export financing in Nigeria; conduct of monetary policy and financial sector reforms; influence of the exchange rate on the economy among others.
Includes bibliographical references and index.
rua 20/10/18
Loans
Keywords: Banks and banking; Finance; Economic policy; Nigeria